Pengembangan Media Pembelajaran Video Tutorial Pada Materi Rias Wajah Panggung Kelas XI SMK Negeri 6 Surabaya - Aisa Nur Layli; Maspiyah; Mutimmatul Faidah; Biyan Yesi Wilujeng (Jurnal Tata Rias, 2025)
The purpose of this project is to produce a video lesson that will function as an instructional tool for stage makeup in SMK Negeri 6 Surabaya's class XI. The five steps of the ADDIE development model—analysis, design, development, implementation, and evaluation—are used in this study's research and development. Expert validation for media elements was 96.88%, material aspects were 96.25%, and language aspects were 95%, according to the study's findings. With an overall average of 96.04%, it falls into the "very suitable" category for educational usage. Additionally, the average value of cognitive learning outcomes was 92.59%, and the students' classical completion rate was 89.44. The psychomotor score, on the other hand, was in the "very good" range with an average of 88.15 and a classical completion percentage of 100%. With 95.3% of pupils responding to the video session, the response rate was deemed "very positive." Thus, it can be said that teaching Balinese dancing stage makeup through video instructional learning materials is quite appropriate and successful. It is expected that this research will serve as a roadmap for the creation of comparable media in the fields of beauty and other occupations. Keywords: Learning Media, Video Tutorial, Stage Makeup, Balinese Pendet Dance